THE ROLE OF UZBEK NATIONAL FOLK GAMES IN SPIRITUAL AND MORAL EDUCATION - Nargiza Isaqova (Research Parks Publishing LLC, 2021)
This article talks about the role of Uzbek national games in spiritual and moral education. The author describes the historical origins of the games in the article.